The effect of molybdenum on the in vitro development of mouse preimplantation embryos. (April 2013) - Bi, Cong-Ming; Zhang, Yu-Ling; Liu, Feng-Jun; Zhou, Tie-Zhong; Yang, Zi-Jun; Gao, Shen-Yang; Wang, Shu-De; Chen, Xiao-Li; Zhai, Xiao-Wei; Ma, Xue-Gang; Jin, Li-Jun; Wang, Shen
<x xml:space="preserve">Abstract</x> The object of this study was to investigate the effect of molybdenum on the development of mouse preimplantation embryos cultured in vitro. Zygotes were flushed from one outbred mouse strain (Kunming), and then were cultured in potassium simplex optimized medium (KSOM) containing 0, 5, 10, 20, 40, 80, 120, and 160 µg/ml of molybdenum for 5 days until the mid-blastocyst stage. The addition of ≤ 20 µg/ml molybdenum did not affect the blastocyst and birth rates. Molybdenum at doses of 40 µg/ml and higher significantly decreased the cleavage, blastocyst and birth rates, the average cell number, and significantly increased the proportion of degenerative blastocysts. At 120 µg/ml molybdenum inhibited the blastocysts development to birth. At 160 µg/ml molybdenum caused overall developmental arrest (up to 16-cells) of embryos and their massive degeneration. In conclusion, molybdenum negatively affected the development of embryos in a dose-dependent manner. With lower doses (≤ 20 µg/ml), mouse embryos were not apparently damaged. With very high doses (≥ 40 µg/ml), embryo quality significantly decreased. This assessment of the effect of molybdenum on the preimplantation embryo is an initial survey of toxicological risk.